EFEKTIVITAS VITARAL MIX TERHADAP KADAR HDL DAN LDL - Syamsianah, Agustin; Anggraini, Herlisa (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Fluctuations in blood glucose levels in Diabetes Mellituspatients to be the main cause of developing complications, due to the formation of free radicals which can lead to oxidative stress. Many studies have been done, but it is still rare that utilize food that can be consumed daily as a source of vegetable-based therapy. Vitaral mix is the formula of food sourced watercress and black rice bran. Watercress contains vary nutrients vitamins B1, B2, C, E, provitamin A, folic acid, protein, glucosinolates, minerals iodine, iron, calcium, and phosphorus. Black rice bran contains anthocyanins were shown to have strong antioxidant activity. This study aimed to analyze the effect of vitaral mix diet to changes in the levels of HDL and LDL cholesterol, which treated on animal models. The results showed that the levels of HDL in the control group is 44.7 ± 2.19 mg / dl during the study, as well as LDL (59.6 ± 2.89 mg / dl). HDL levels in the group of diabetic rats increased 3.4 ± 2.99 mg / dL, while elevated LDL levels is 19.6 ± 11.33 mg / dl. HDL levels of diabetic rats with vitaral mix diet increased significantly during the study amounted to 53.9 ± 3.59 mg / dl, but LDL levels decrease with 9.9 ± 5.72 mg / dl.Keywords:vitaral mix, HDL, LDL